The Impact of Learnings Media and Criticals Thinking Ability for the Students Achievement of Social Subject Grade VIII SMP Cinta Rakyat 3 Pematang Siantar Year 2022/2023 - Anjali G.B Manalu; Anggun Tiur Ida Sinaga; Benjamin A. Simamora (International Journal of Integrated Science and Technology, 2023)
This type of research is quantitative research with a quantitative descriptive data analysis approach. The research population was students at the private preparatory vocational school Pematang Siantar with a total of 160 students. The research sample consisted of 115 students. The sampling technique used was random sampling by the researcher according to the class at school. The data collection technique used was a questionnaire. The hypothesis generation technique uses multiple regression analysis and the coefficient of determination (R2). The research results show that: 1) there is a positive and significant influence of learning media on learning achievement. This result can be seen in the t test where the calculated t value of learning media is (4.636) > t table value (1.65845) which means that this variable is significant . 2) there is a positive and significant influence of critical thinking skills on learning achievement. This result can be seen in the t test where and the calculated t value of critical thinking skills (2.133) > t table (1.65845) which means that this variable is significant. 3) learning media and critical thinking skills together influence learning achievement. This result can be seen in the F test where the Fcount value (11.735) > Ftable value (3.08). The R Square coefficient of determination test was found to be 0.1173, which means that 17.3% of the learning media variables and critical thinking skills influence student learning achievement at the Cinta Rakyat 3 Pematang Siantar Private Middle School and the remaining 82.7% is the influence of other variables that are not examined in this research.